Weight loss over time and survival: a landmark analysis of 1000+ prospectively treated and monitored lung cancer patients. Issue 6 (17th September 2020) - Le‐Rademacher, Jennifer; Lopez, Camden; Wolfe, Eric; Foster, Nathan R.; Mandrekar, Sumithra J.; Wang, Xiaofei; Kumar, Rajiv; Adjei, Alex; Jatoi, Aminah
Abstract: Background: Eligibility criteria and endpoints for cancer cachexia trials—and whether weight loss should be included—remain controversial. Although most cachexia trials enrol patients after initial cancer diagnosis, few studies have addressed whether weight loss well after a cancer diagnosis is prognostic. Methods: We pooled data from non‐small cell lung cancer patients from prospectively conducted trials within the Alliance for Clinical Trials in Oncology (1998–2008), a nationally funded infrastructure. We examined (i) weight data availability and weight changes and (ii) survival. Results: A total of 822 patients were examined. Of these, 659 (80%) were on treatment at the beginning of Cycle 2 of chemotherapy; weight was available for 656 (80%). By Cycles 3 and 4, weight was available for 448 (55%) and 384 (47%), respectively. From baseline to immediately prior to Cycle 2, 208 (32%) gained weight; 225 (34%) lost <2% of baseline weight; and 223 (34% of 656) lost 2% or more. Median survival from the beginning of Cycle 2 was 13.0, 10.9, and 6.9 months for patients with weight gain, weight loss of <2%, and weight loss of 2% or more, respectively. In multivariate analyses, adjusted for age, sex, performance score, type of treatment, and body mass index, weight loss of 2% or more was associated with poor overall survival compared with weight gain [hazard ratio (HR) = 1.66; 95% confidence interval (CI): 1.33–2.07; P  < 0.001] and compared with weight loss of <2% (HR = 1.57; 95% CI: 1.27–1.95; P  < 0.001). Although weight loss of <2% was not associated with poorer overall survival compared with weight gain, it was associated with poorer progression‐free survival (HR = 1.24; 95% CI: 1.01–1.51; P  = 0.036). Similar findings were observed in a separate 255‐patient validation cohort. Conclusions: Weight should be integrated into cancer cachexia trials because of its ease of frequent measurement and sustained prognostic association.